The effect of Staphylococcus aureus on innate and adaptive immunity and potential immunotherapy for S. aureus-induced osteomyelitis - Chen, Yingqi; Liu, Zixian; Lin, Zexin; Lu, Mincheng; Fu, Yong; Liu, Guanqiao; Yu, Bin (Frontiers in Immunology, 2023)
Osteomyelitis is a chronic inflammatory bone disease caused by infection of open fractures or postoperative implants. Particularly in patients with open fractures, the risk of osteomyelitis is greatly increased as the soft tissue damage and bacterial infection are often more severe. Staphylococcus aureus, one of the most common pathogens of osteomyelitis, disrupts the immune response through multiple mechanisms, such as biofilms formation, virulence factors secretion and metabolic patterns alteration, which attenuates the effectiveness of antibiotics and surgical debridement toward osteomyelitis. In osteomyelitis, immune cells such as neutrophils, macrophages and T cells are activated in response to pathogenic bacteria invasion with excessive inflammatory factors secretion, immune checkpoints overexpression and downregulation of immune pathway transcription factors, which enhances osteoclastogenesis and results in bone destruction. Therefore, the study of the mechanisms of abnormal immunity will be a new breakthrough in the treatment of osteomyelitis.